Peers as Law Enforcement Support (PALS): An early prevention program. (September 2019) - Van Hasselt, Vincent B.; Klimley, Kristin E.; Rodriguez, Samantha; Themis-Fernandez, Maureen; Henderson, Sarah N.; Schneider, Barry A.
Abstract: Police officers encounter a variety of stressors, most of which are unique to the profession. These can exact a toll on an officer's mental health, and leave them at increased risk for experiencing psychological problems. However, due to stigma surrounding mental health, as well as traditional law enforcement culture, many officers find it difficult to report, or seek help for, difficulties due to fear of repercussions and/or distrust. Consequently, the potential value of incorporating trained peers as a "first line of defense" has received increased attention. This article describes the Peers as Law Enforcement Support (PALS) program developed in a collaboration between a local police agency and University psychology department. Results of a pilot study evaluating participants' perspectives on course content and quality of instruction are presented. Finally, the need for a broad spectrum approach to prevention and intervention of mental health issues in officers is underscored. Highlights: Police officers' unique occupational stressor's impact their mental health. The PALS program was developed as a secondary prevention effort. Officers viewed PALS as practical in the learning of material/skills. Trainers were prepared, engaging, knowledgeable, and encouraging.